2017
DOI: 10.1136/jnnp-2017-316174
|View full text |Cite
|
Sign up to set email alerts
|

TBK1mutations in Italian patients with amyotrophic lateral sclerosis: genetic and functional characterisation

Abstract: Background TANK-binding kinase 1 (TBK1) gene has been recently identified as a causative gene of amyotrophic lateral sclerosis (ALS).MethodsWe sequenced the TBK1 gene in a cohort of 154 Italian patients with ALS with unclear genetic aetiology. We subsequently assessed the pathogenic potential of novel identified TBK1 variants using functional in vitro studies: expression, targeting and activity were evaluated in patient-derived fibroblasts and in cells transfected with mutated-TBK1 plasmids.ResultsWe identifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 31 publications
(36 reference statements)
1
29
0
Order By: Relevance
“…In this study, we screened a Chinese cohort of 270 cases with ALS, FTD, FTD-ALS (or ALS-FTD) for TBK1 mutations and identified two novel frame-shift TBK1 mutations (p.E653fs and p.L688Rfs*14) in a sporadic case with SD-ALS and an ALS-FTD family respectively, accounting for 0.7% of total cases, which were consistent with the recent Asian population studies from Taiwan (0.5%; 1/207 ALS) and China (0.7%; 2/294 ALS) [ 17 , 18 ], although they were significantly lower than European cohorts, such as Italian (3.2%; 5/154 ALS) and Belgian (1.7% 11/629 ALS, FTD, FTD-ALS) [ 19 , 20 ]. Our results further indicated that the TBK1 gene was not a common gene in the Chinese population.…”
Section: Discussionsupporting
confidence: 88%
“…In this study, we screened a Chinese cohort of 270 cases with ALS, FTD, FTD-ALS (or ALS-FTD) for TBK1 mutations and identified two novel frame-shift TBK1 mutations (p.E653fs and p.L688Rfs*14) in a sporadic case with SD-ALS and an ALS-FTD family respectively, accounting for 0.7% of total cases, which were consistent with the recent Asian population studies from Taiwan (0.5%; 1/207 ALS) and China (0.7%; 2/294 ALS) [ 17 , 18 ], although they were significantly lower than European cohorts, such as Italian (3.2%; 5/154 ALS) and Belgian (1.7% 11/629 ALS, FTD, FTD-ALS) [ 19 , 20 ]. Our results further indicated that the TBK1 gene was not a common gene in the Chinese population.…”
Section: Discussionsupporting
confidence: 88%
“…In ALS patients, nonsense and frameshift variants in TBK1 act through a haploinsufficiency mechanism. Cellular studies have been performed to better characterize the role of missense variants, demonstrating that missense variants affect phosphorylation of IRF3, a TBK1 target, OPTN binding and phosphorylation, as well as autophosphorylation of TBK1 [ 89 , 143 ]. The mechanism underlying TBK1 pathogenesis can be considered the same for nonsense and missense variants, especially when located in critical domains.…”
Section: Applying the Acmg Standards And Guidelines For The Interpmentioning
confidence: 99%
“…Most notably, two recent studies have identified TBK1 as a novel amyotrophic lateral sclerosis (ALS) and frontotemporal dementia (FTD) causative gene [7,8]. Additional TBK1 mutations characterized by strong penetrance have been disclosed in distinct cohorts of ALS and FTD patients [9][10][11][12].…”
mentioning
confidence: 99%